STUDI KELELAHAN KERJA SUBYEKTIF PADA PEKERA SEKTOR INFORMAL : KAJIAN PUSTAKA - Baskara Petra Marhaensa; Yuliani Setyaningsih; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Abstract: Fatigue is a protective mechanism released by human’s body to avoid further damage, so then after resting the body will experience recovery. Fatigue can affect a person's ability to think clearly and respond appropriately, and also is related to injuries that can occur at work. This study aims to describe the physical workload, nutritional status, and hydration status with fatigue in informal sector workers. The method used in this research is literature study, conducted online through several trusted websites or internet sites such as Sciendirect, JSTOR, ProQuest, Cambridge Core, Scopus, and Google Schoolar. This research was conducted on 20 articles consisting of 15 national articles and 5 international articles. Articles are analyzed by data extraction and processed through stages in the form of organizing, synthesizing, identifying, and formulating. The results of this research based on 20 articles, showed there was a relationship between physical workload and fatigue in all articles, five of the eight articles did not have a relationship between nutritional status with fatigue, and four out of five articles had a relationship between hydration status and work fatigue on workers in informal sectorKeywords : Worker Fatigue, Physical Workload, Nutritional Status, Hydration Status, Informal Sector Workers